Tied with twine : a novel - Records, Pam (2019)
"A young Polish American woman who has been saving her poker winnings for a train ticket and a chance to be anything other than an immigrant's daughter, Halina knows that Prohibition stinks to high heaven and then some. But her plans are interrupted when whiskey men come to town, hiding their bootleg liquor in the cellar of the abandoned house next door. Suddenly, the small immigrant community is the backdrop for conniving schemes and escalating violence as rival bootleggers take over the streets. Seeing a glimpse of the future, Baba, the aging mystic, realizes it's time for Halina to take over as town healer and become the one to dispense the Old Country poultices and potions to those who are ailing. But Halina isn't sure she wants the job. Can she treat knife wounds, burns, and blindness from a bad batch of hooch? As she faces her most difficult case yet, Halina must decide just how far she will go to save a dying patient, and learns that healing isn't just about medicine and bandages, but it's also about something much stronger: hope."–Back cover